1996
DOI: 10.1007/bf00333225
|View full text |Cite
|
Sign up to set email alerts
|

Fine litter input to terrestrial humus forms in Colombian Amazonia

Abstract: A comparative litter fall study was made in five rain forest stands along a gradient of humus form development and soils in the Amazon lowlands of eastern Colombia. The total fine litter fall was highest in a plot on a well drained soil of the flood plain of the Caquetfi River (1.07 kg • m -2 • y-l), lower in three plots on well drained upland soils (0.86, 0.69, and 0.68 kg • m -2 • y-l), and lowest in a plot on a poorly drained, upland podzolised soil (0.62 kg • m -2 • y-l). In the four upland plots, leaf lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
2
9
0
4
Order By: Relevance
“…The necromass on the Lambir sandstone soil also had higher Mg:Ca ratios than in many other tropical forests, although similar to those in other Bornean MDF soils on Tertiary clastic sediments (Burghouts et al 1998, Proctor et al 1983. However, because of its great lability and copious leaching from forest canopies, necromass concentrations of K vary widely in tropical forests, and the Lambir values are not particularly high (Lips & Duivenvoorden 1996). Overall, the distinctive lithogenic nutrient stoichiometry of the Lambir soils persists in the fresh litter and necromass, but with diminishing clarity at each stage.…”
Section: Discussionsupporting
confidence: 50%
“…The necromass on the Lambir sandstone soil also had higher Mg:Ca ratios than in many other tropical forests, although similar to those in other Bornean MDF soils on Tertiary clastic sediments (Burghouts et al 1998, Proctor et al 1983. However, because of its great lability and copious leaching from forest canopies, necromass concentrations of K vary widely in tropical forests, and the Lambir values are not particularly high (Lips & Duivenvoorden 1996). Overall, the distinctive lithogenic nutrient stoichiometry of the Lambir soils persists in the fresh litter and necromass, but with diminishing clarity at each stage.…”
Section: Discussionsupporting
confidence: 50%
“…On the basis of their horizons the humus forms we described under rock savanna belong to a group of tropical humus forms on nutrient-depleted or rocky substrates, which are characterized by the accumulation of faunal excrements within a dense root mat, without or with a poor incorporation of organic matter to the mineral soil (Lips and Duivenvoorden, 1996;Loranger et al, 2003). They share common features with moder which has been described in temperate regions (Green et al, 1993).…”
Section: The Sequence Of Soil Development On the Nouragues Inselbergmentioning
confidence: 90%
“…Despite the widely reported lack of organic matter and nutrients in tropical soils, due to rapid mineralization of leaf and root litter and intense leaching (Lavelle, 1984;Lavelle et al, 1993), huge accumulations of organic matter can be observed on rocky substrates and nutrientdepleted sandy soils (Lips and Duivenvoorden, 1996;Loranger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although leaf‐fall rates peak during the dry season (Wieder & Wright 1995), the larger return of nutrients from forest trees to the forest floor during the wet season than during the dry season (Table 1) coincides with 65% of the annual leaf‐fall during the longer wet season. Overall, nutrient return in leaf‐fall was at the high end of values published in reports for other lowland tropical forests (Lips & Duivenvoorden 1996); in a large part, this reflects the large litter mass in the study area.…”
Section: Discussionmentioning
confidence: 48%
“…The question of whether nutrient concentrations in leaf‐fall vary systematically with seasonal drought in tropical forests is still open to debate. Some have concluded that nutrient concentrations in leaf‐fall vary haphazardly during the year (Lips & Duivenvoorden 1996; Herbohn & Congdon 1998). In contrast, others have found relatively strong evidence for lower K concentrations and greater N concentrations in wet‐season leaf‐fall (Scott et al .…”
Section: Discussionmentioning
confidence: 99%